A COMPRESSION-EXTENSION INTERACTION ON THE SIBIRIAN-MONGOLIAN BORDER. PRELIMINARY ANALYSIS OF RECENT AND ACTUAL DEFORMATIONS IN THE TUNKA BASIN - Larroque C.; Stéphan J.-F.; Calais É.; Déverchère J.; Loncke L.; Ritz J.-F.; San'kov V.; Arjannikova A. (My University, 2001)
The Tunka basin was initiated during Oligocene, under transtensional regime (normal-sinistral) as shown by large-scale structures and geomorphology. Nevertheless, a preliminary analysis of the most recent deformations allows us to evidence transpression on several sites within the basin. These tectonic features together with focal mechanisms and preliminary GPS data, suggest that the kinematics of the Tunka basin has undergone a very recent change, which could be due to the northward propagation of the India-Eurasia collisional strain field.
Keywords: active tectonic; structural heritage; Mongolia; Baikal